Freedom of Religion and Belief in International Documents and National Legislation - Mariam Adamashvili (European Scientific Journal, ESJ, 2025)
Human rights are protected by various international documents, reinforced by numerous legal acts and national legislation, underscoring their importance for individuals and, more broadly, for the development of each state. The extent to which human rights are effectively ensured, realized, and exercised within a state is directly linked to the degree of its democracy. Freedom of belief, religion, and conscience is among the most fundamental rights upon which the concept of a legal and democratic state is built. This right plays a crucial role in establishing religious and, more generally, democratic pluralism, which is essential for maintaining public peace and harmony. Therefore, this paper focuses on examining freedom of religion and belief as reflected in international documents and national legislation.